Fudge-a-mania - Blume, Judy. (New York : Dutton Children's Books, 1990)
Pete describes the family vacation in Maine with the Tubmans, highlighted by the antics of his younger brother Fudge.
490
Maine Student Book Award winner, 1991-1992
Keywords: Brothers and sisters -- Juvenile fiction; Vacations -- Fiction; Brothers -- Fiction; Family life -- Fiction; Humorous fiction